Android based real time advance security for parking system in IOT - Venkata Sai Kasturi Babu, CH; Athuluri, Manikanta; Venkatram, N (International Journal of Engineering and Technology, 2018)
In recent trends traffic has become a major problem in most of the cities. There are limited car parking facilities and less road safety precautions observed. So, to address the traffic problems are being made in the field of IoT.Â Â Â This paper will present the basic idea of cloud-based parking system. Cloud will store and process the data between device and mobile. In cloud, stored files will be obtained from anywhere through the network connection. By using the latest technology called IoT for smart cities, we can book the parking slot of a vehicle from anywhere. We need to take registration details for reserving the parking slot and for security purpose we are generating an OTP. By using the OTP, we can book our slot through an android application.